Security sharing scheme for encrypted data in cloud storage - Wen-bin YAO; Si HAN; Xiao-yong LI (Tongxin xuebao)
With the convenient of storing and sharing data in cloud storage environment,the concerns about data security arised as well.To achieve data security on untrusted servers,user usually stored the encrypted data on the cloud storage environment.How to build a cipertext-based access control scheme became a pot issue.For the access control problems of ciphertext in cloud storage environment,a CP-ABE based data sharing scheme was proposed.Novel key generation and distribution strategies were proposed to reduce the reliance on a trusted third party.Personal information was added in decryption key to resistant conclusion attacks at the same time.Moreover,key revocation scheme was proposed to provide the data backward secrecy.The security and implement analysis proves that proposed scheme is suit for the real application environment.